Răspunsuri

Cel mai inteligent răspuns!
2014-10-11T15:20:33+03:00
A comuta vine de la comutativitate, adica a+b=b+a

  \left[\begin{array}{ccc}0&1\\1&2\\\end{array}\right] +   \left[\begin{array}{ccc}-3&2\\2&1\\\end{array}\right] =   \left[\begin{array}{ccc}-3&3\\3&3\\\end{array}\right]

  \left[\begin{array}{ccc}-3&2\\2&1\\\end{array}\right] +   \left[\begin{array}{ccc}0&1\\1&2\\\end{array}\right]  =   \left[\begin{array}{ccc}-3&3\\3&3\\\end{array}\right]

din cele doua rezulta ca a+b =b+a = x

3 3 3